Students perspective on sustainable tropical architectural ideas - Ahmad, Mohd. Hamdan (2005)
Books on tropical architecture normally based on the architectural idea as revealed by the traditional architecture solutions. The environment during that time was different. It was less developed thus was more natural. The less complex building scale seem to fit nicely within the environment that somehow act naturally as part of the building sheltering system. The same location has now changed due to rapid development. The contemporary architecture now must response to totally different needs and changed surrounding. High density, complexities and energy demand are new design issues. These new scenarios require new architectural solutions. This paper shares some brave attempts by architecture students from EnviroUnit within the School of Architecture in Universiti Teknologi Malaysia to create sustainable contemporary tropical architecture. Their exploration of architectural design ideas ranges from less complex building to resort development and high density urban housing. It is the hope of the author that they become the future architects who will repair the damaged done for more sustainable tropical environment and tropical urban cities.